Urban Soils in Gainesville, Florida and Their Implications for Environmental Quality and Management (2011)
Urban planners, environmental scientists, and land managers in Florida are increasingly aware of the ecosystem services provided by the trees and shrubs that comprise an urban forest (Escobedo et al. 2010, http://edis.ifas.ufl. edu/document_fr276). Yet soils, which form an essential part of the urban ecosystem and provide many important ecosystem services as well, remain largely overlooked (Hagan et al. 2010). Since many urban soils in Florida are highly modified and/or made of fill brought from elsewhere, it is frequently assumed that they are homogenous, heavily disturbed, or of low fertility. Soil survey maps or urban forest assessments do not even describe urban soils, delineating them instead as blank areas on the landscape or focusing solely on individual tree soil requirements (http:// edis.ifas.ufl.edu/document_fr276). Recent studies, however, have found that urban soils are highly variable, ranging from highly modified to nearly undisturbed. Nonetheless, certain trends and patterns in urban soil characteristics have been observed (Pouyat et al. 2007). This publication will shed light on how and why soil properties vary across Gainesville and provide useful information on the sustainable management of urban soils. It is meant to complement the more general overview of Florida’s urban soils given in Hagan et al. (2010). Gainesville provides a good example of how soils in north central Florida are affected by urbanization. It is a medium-sized city (approximately 131,591 residents) and has been experiencing urban sprawl into agricultural and forested areas in recent years. For this publication, we used field sampling, interprolation (a method of predicting a value for a parameter in unsampled locations from known values in sampled locations), and Geographical Information Systems to map and provide a city-level overview of four key soil properties in Gainesville—bulk density, phosphorus, organic matter content, and pH—and we explain how they vary according to land use. As part of a larger urban ecosystem study, surface soil samples were collected from random locations from five different land uses across Gainesville: commercial, forested, institutional, residential, and vacant (Figures 1 and 2) and analyzed at the University of Florida’s Analytical Services Laboratory (Dobbs-Brown, 2009; Escobedo et al. 2010; http://edis.ifas. ufl.edu/document_fr276). Note, for the purposes of this study, vacant areas were defined as abandoned sites with no existing urban infrastructure. While the properties of deeper soils are important, we chose to focus solely on the uppermost 10 centimeters of the soil profile, to minimize disturbance and damage (underground utilities, lawns, etc.)